INFLUENCE OF FAMILY DYNAMICS ON STUDENTS’ BEHAVIOR: CHALLENGES AND OPPORTUNITIES - Billanes, Freddie B. (President University, 2024)
Family dynamics impact comfort and happiness. 801 students were surveyed using a descriptive correlational study and 0.897-reliable researcher-made questionnaire. The study found that open communication, quality time, respect, responsibility, and supporting a peacemaker during tough times strengthened family ties. Parental honesty and dependability were closest. Most families have money and work-life issues. Number of children, family members' traits, parents' connection, and gentle or hard upbringing affected family dynamics. Family relationships are less impacted by the